Targeting interferon response genes sensitizes aromatase inhibitor resistant breast cancer cells to estrogen-induced cell death. Issue 1 (December 2015) - Choi, Hye; Lui, Asona; Ogony, Joshua; Jan, Rifat; Sims, Peter; Lewis-Wambi, Joan
Abstract Introduction Estrogen deprivation using aromatase inhibitors (AIs) is currently the standard of care for postmenopausal women with hormone receptor-positive breast cancer. Unfortunately, the majority of patients treated with AIs eventually develop resistance, inevitably resulting in patient relapse and, ultimately, death. The mechanism by which resistance occurs is still not completely known, however, recent studies suggest that impaired/defective interferon signaling might play a role. In the present study, we assessed the functional role of IFITM1 and PLSCR1; two well-known interferon response genes in AI resistance. Methods Real-time PCR and Western blot analyses were used to assess mRNA and protein levels of IFITM1, PLSCR1, STAT1, STAT2, and IRF-7 in AI-resistant MCF-7:5C breast cancer cells and AI-sensitive MCF-7 and T47D cells. Immunohistochemistry (IHC) staining was performed on tissue microarrays consisting of normal breast tissues, primary breast tumors, and AI-resistant recurrence tumors. Enzyme-linked immunosorbent assay was used to quantitate intracellular IFNα level. Neutralizing antibody was used to block type 1 interferon receptor IFNAR1 signaling. Small interference RNA (siRNA) was used to knockdown IFITM1, PLSCR1, STAT1, STAT2, IRF-7, and IFNα expression. Results We found that IFITM1 and PLSCR1 were constitutively overexpressed in AI-resistant MCF-7:5C breast cancer cells and AI-resistant tumors and that siRNA knockdown of IFITM1 significantly inhibited the ability of the resistant cells to proliferate, migrate, and invade. Interestingly, suppression of IFITM1 significantly enhanced estradiol-induced cell death in AI-resistant MCF-7:5C cells and markedly increased expression of p21, Bax, and Noxa in these cells. Significantly elevated level of IFNα was detected in AI-resistant MCF-7:5C cells compared to parental MCF-7 cells and suppression of IFNα dramatically reduced IFITM1, PLSCR1, p-STAT1, and p-STAT2 expression in the resistant cells. Lastly, neutralizing antibody against IFNAR1/2 and knockdown of STAT1/STAT2 completely suppressed IFITM1, PLSCR1, p-STAT1, and p-STAT2 expression in the resistant cells, thus confirming the involvement of the canonical IFNα signaling pathway in driving the overexpression of IFITM1 and other interferon-stimulated genes (ISGs) in the resistant cells. Conclusion Overall, these results demonstrate that constitutive overexpression of ISGs enhances the progression of AI-resistant breast cancer and that suppression of IFITM1 and other ISGs sensitizes AI-resistant cells to estrogen-induced cell death.